Fatigue strength of severely notched specimens made of Ti–6Al–4V under multiaxial loading. Issue 5 (19th December 2014) - Berto, F.; Campagnolo, A.; Lazzarin, P.
Abstract The present paper deals with multiaxial fatigue behaviour of severely notched components made of titanium grade 5 alloy (Ti–6Al–4V). The experimental tests have been carried out under combined Mode I and Mode III loadings, both in phase and out of phase. Cylindrical specimens weakened by circumferential notches have been employed. Different nominal load ratios have been applied in the tests (R = −1, 0 and 0.5). The specimens had a notch‐tip radius smaller than 0.1 mm, a notch depth equal to 6 mm and an opening angle of 90°. The results obtained by multiaxial fatigue testing are depicted in comparison with data from pure modes of loading on smooth and notched samples, characterized by a load ratio in the range −3 ≤ R ≤ 0.5. A large bulk of new fatigue data (more than 160) is summarized in the manuscript. The data are first plotted in terms of the nominal stress amplitudes, and then they are reanalysed by means of the local energy measured in the control volumes surrounding the notch tip. The dependence of the size of the control radius as a function of the loading mode is analysed. A very different behaviour is found for tension and torsion, corresponding to a different notch sensitivity.